Radical surgery of oligometastatic pancreatic cancer - Hackert, Thilo; Niesen, Willem; Hinz, Ulf; Tjaden, Christin; Strobel, Oliver; Ulrich, Alexis; Michalski, Christoph; Büchler, Markus W. (European journal of surgical oncology, 2017)
Background: In metastatic disease (M1), chemotherapy (expected survival: 6-10 months) is considered the only treatment option. The aim of this study was to evaluate the outcome of curative M1 PDAC resections. Methods: Prospective data of all patients undergoing primary tumour and metastasis resection for stage IV PDAC during a 12-year period was analysed regarding localisation (liver or distant interaortocaval lymph nodes; ILN), morbidity and survival. Patients were stratified with regard to syn- or metachronous metastases resection. Results: Patients (n = 128) undergoing PDAC and metastases resection (intention-to-treat, oligometastatic stage; liver n = 85; ILN n = 43) were included. Surgical morbidity and 30-day mortality after synchronous resection of M1 tumours were 45% and 2.9%, respectively. Overall median survival after M1 resection was 12.3 months in both groups. Long-term outcome showed a 5-year survival of 8.1% after surgery for both liver metastases and 10.1% following ILN resection. Conclusions: The present collective is the largest series of resected metastatic PDAC and shows that resection of liver or ILN metastases can be done safely and should be considered as it may be superior to palliative treatment, and it is associated with long-term survival of 10% in selected patients. Further studies to stratify patients for these procedures are warranted.
Available online 9 November 2016
Gesehen am 20.09.2018